Audit of performance of regional ECV services against RCOG standards. (7th June 2011) - Banks, C; Moss, H; Ferguson, E; Gibson, J
Abstract : Introduction: Breech presentation complicates 3–4% of all deliveries. Vaginal breech delivery is associated with increased risk to the fetus. External cephalic version (ECV) can avoid the need for caesarean section. The RCOG Green top guideline (No.20a) promotes the use of ECV to this aim. Aim: To evaluate the success and practice of ECV within our four regional maternity units. Method: Retrospective review of an annual cohort of breech presentation at ≥36 weeks gestation. Results: 194 pregnancies were identified. 158 (81%) women were offered an ECV. The proportion of women documented to receive the recommended information on the benefits of ECV differed widely between units (8–96%). 70% of those not offered ECV had more than one relative contraindication or an absolute contraindication. 85 women accepted ECV. 44 (52%) received tocolytics. 35 women (41%) had a successful version. Maternal body mass index and parity, but not tocolysis, influenced success. Conclusion: Successful ECV is associated with a high chance of vaginal delivery. However, only 11% of women with a breech presentation at term appeared to have avoided CS as the result of our ECV service. Clinical management will be improved by the introduction of a standardised information/consent document. Non-selective use of tocolysis may be beneficial.